EPIDEMIOLOGICAL PROFILE OF PATIENTS IN THE INTENSIVE THERAPY UNIT - Sobral Silva do Nascimento, Andresa; Pereira da Silva, Eliane; Rayssa da Silva Góes, Maria; Carla Alves de Souza santos, Rilda; Conceição Alves Leite Pereira do Lago, Vivian (Health and Society, 2023)
Objective: To know the profile of intensive care users according to published literature. Methods: it is an integrative review of literature, from the search of scientific articles, in the databases SciELO, Lilacs, Bireme, with the search of data between the years 2014 to 2019. Results: There were found 644 articles and remained only four, where they identified that in Brazil, the elderly male patients with respiratory disorders occupy about 42% to 52% of the ICU hospitalizations and spend approximately 60% of the existing ones. Conclusion: In this way it is relevant that the nursing has knowledge of the characteristics and profile presented by the patients, of the intensive therapy in order to respond with greater agility to the patients’ demands.